Congenital anomalies in the offspring of occupationally exposed mothers: a systematic review and meta-analysis of studies using expert assessment for occupational exposures. Issue 5 (30th March 2019) - Spinder, N; Prins, J R; Bergman, J E H; Smidt, N; Kromhout, H; Boezen, H M; de Walle, H E K
Abstract: STUDY QUESTION: Is there an association between maternal occupational exposure to solvents, pesticides and metals as assessed by expert-based assessment and congenital anomalies in the offspring? SUMMARY ANSWER: There is an association between maternal occupational exposure to solvents and congenital anomalies in the offspring, including neural tube defects, congenital heart defects and orofacial clefts. WHAT IS KNOWN ALREADY: One important environmental risk factor for development of congenital anomalies is maternal occupational exposure to chemicals in the workplace prior to and during pregnancy. A number of studies have assessed the association with often conflicting results, possibly due to different occupational exposure assessing methods. STUDY DESIGN, SIZE, DURATION: For this systematic review with meta-analysis, the search terms included maternal occupation, exposure, congenital anomalies and offspring. Electronic databases MEDLINE and EMBASE were searched for English studies up to October 2017. PARTICIPANTS/MATERIALS, SETTING, METHODS: Two reviewers independently screened all citations identified by the search. Case-control studies and cohort studies were included if (I) they reported on the association between maternal occupational exposure to solvents, pesticides or metals and congenital anomalies, and (II) assessment of occupational exposure was performed by experts. Data on study characteristics, confounders and odds ratios (ORs) were extracted from the included studies for four subgroups of congenital anomalies. Methodological quality was assessed using the Newcastle-Ottawa Scale. In the meta-analysis, random effects models were used to pool estimates. MAIN RESULTS AND THE ROLE OF CHANCE: In total, 2806 titles and abstracts and 176 full text papers were screened. Finally, 28 studies met the selection criteria, and 27 studies could be included in the meta-analysis. Our meta-analysis showed that maternal occupational exposure to solvents was associated with neural tube defects (OR: 1.51, 95%CI: 1.09–2.09) and congenital heart defects (OR: 1.31, 95%CI:1.06–1.63) in the offspring. Also maternal occupational exposure to glycol ethers, a subgroup of solvents, was associated with neural tube defects (OR: 1.93, 95%CI: 1.17–3.18) and orofacial clefts (OR: 1.95, 95%CI: 1.38–2.75) in the offspring. Only one study investigated the association between maternal occupational exposure to solvents and hypospadias and found an association (OR: 3.63, 95%CI: 1.94–7.17). Results of the included studies were consistent. In our meta-analysis, we found no associations between occupational exposure to pesticides or metals and congenital anomalies in the offspring. LIMITATIONS, REASONS FOR CAUTION: A limited number of studies was included, which made it impossible to calculate pooled estimates for all congenital anomalies, analyse individual chemicals or calculate exposure–response relations. Bias could have been introduced because not all included studies corrected for potentially confounding factors. WIDER IMPLICATIONS OF THE FINDINGS: Employers and female employees should be aware of the possible teratogenic effects of solvent exposure at the workplace. Therefore, is it important that clinicians and occupational health specialist provide women with preconception advice on occupational solvent exposure, to reduce the congenital anomaly risk. STUDY FUNDING/COMPETING INTEREST(S): NSp was paid by the Graduate School of Medical Sciences (MD/PhD program), UMCG, Groningen, the Netherlands. EUROCAT Northern Netherlands is funded by the Dutch Ministry of Health, Welfare and Sports. There are no competing interests. REGISTRATION NUMBER: CRD42017053943.